Analisis Semiotik pada Jurnalistik Foto “Melihat Momen Unik Deklarasi Kampanye Damai Idi Media Online detik.com” - Arsa Widitiarsa Utoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Journalistic photos in online mass media are displayed with the aim of strengthening and visualizing the contents of the news. Therefore, journalistic photos in the newspaper have a role in involving feelings and arousing the emotions of readers. This research aims to analyze on how a message icon be known by its meaning both seen from the true meaning (denotative) and the meaning implied in it (connotative). To find the meaning contained in journalistic photographs, the author uses the semiotic approach. Semiotic analysis is a method for analyzing and giving meanings it symbols contained in a message or text symbol. The application if semiotics in intersexuality is an interaction between texts and thoughts contained in the narrative. A safe and peaceful general election discourse can be seen from the photo.